Eating Habits, Lifestyle and Friends Associated with the Incidence of Adolescent Overnutrition at Bengkulu - Rizki, Gibrina; Maigoda, Tonny Cortis; Okfrianti, Yenni; Witradharma, Tetes Wahyu; Sari, Ayu Pravita; Hari Hariadi (Research and Social Study Institute, 2024)
Adolescents today are increasingly at risk of becoming overweight, largely due to factors related to food consumption and lifestyle. This study aimed to determine the relationship between night eating habits, sedentary behavior, and peer influence with the incidence of overweight among adolescents at SMA Negeri 07 Bengkulu City in 2024. This research was conducted using an analytic observational design with a cross-sectional approach. The sample consisted of 54 grade XI students, selected through proportional stratified random sampling. Night eating habits were assessed using a 3x24-hour recall form supplemented with food photographs, sedentary behavior was measured using the Adolescent Sedentary Activity Questionnaire (ASAQ), and peer influence was evaluated through a structured questionnaire. Data were analyzed using univariate and bivariate techniques, processed with SPSS software, and assessed with the chi-square test at a significance level of α = 0.05. The findings revealed that a significant proportion of respondents exhibited frequent night eating habits (44.4%, p = 0.002), high levels of sedentary behavior (44.4%, p = 0.006), and were significantly influenced by their peers (61.1%, p = 0.004). The study concludes that there is a significant association between night eating habits, sedentary behavior, and peer influence with the incidence of overweight among adolescents at SMA Negeri 07 Bengkulu City.